Tutorial Video Media of How to Make Dolls from Socks for Students with Intelectual Disability - Restu Emidal Putri; Mega Iswari (Department of Special Education, 2019)
This research aims at improving students learning ability using video tutorial in making dolls using socks. Quasi-experiment design is conducted with pre-test and post-test, and data is analyzed using the Mann-Whitney test. The results of the research show that video tutorial is effective to improve the skills of intellectually disabled children in making dolls using socks